Comprehensive Analyses of the Complete Mitochondrial Genome of Figulus binodulus (Coleoptera: Lucanidae). Issue 5 (25th September 2020) - Lee, Jungmo; Park, Jonghyun; Xi, Hong; Park, Jongsun
Abstract: Figulus binodulus Waterhouse is a small stag beetle distributed in East Asia. We determined the first mitochondrial genome of F. binodulus of which is 16, 261-bp long including 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNAs, and a single large noncoding region of 1, 717 bp. Gene order of F. binodulus is identical to the ancestral insect mitochondrial gene order as in most other stag beetle species. All of 22 tRNAs could be shaped into typical clover-leaf structure except trnSer1 . Comparative analyses of 21 Lucanidae mitochondrial genomes was conducted in aspect of their length and AT-GC ratio. Nucleotide diversities analyses provide that cox1 and cox2 in Lucanidae are less diverse than those of Scarabaeoidea. Fifty simple sequence repeats (SSRs) were identified on F. binodulus mitochondrial genome. Comparative analysis of SSRs among five mitochondrial genomes displayed similar trend along with SSR types. Figulus binodulus was sister to all other available family Lucanidae species in the phylogenetic tree.